Speech performance in language teaching-learning: Culturally textual and non-textual landscapes of Toba Caldera Geosites - Robert Sibarani; Mangatur Nababan; Wahyudi Wahyudi; Defri Elias Simatupang; Yessy Octavianna (Studies in English Language and Education, 2024)
The study described teachers speech performance using textual and non-textual elements in language teaching-learning. The linguistic element is the text of the language landscape of Toba Caldera Geosites. This research was conducted from the philosophical perspective of empiricism that is relevant to the phenomenological paradigm, with the type of interpretative and constructive phenomenology underlying the qualitative design. The qualitative design model applied in this research was phenomenology, aiming to understand and describe individuals subjective experiences and perspectives. The data were collected through in-depth interviews, focused group discussions, and direct participatory observation. The procedure covered (1) establishing the objectives of the study and bracketing, (2) locating participants or informants, (3) data collection, (4) transcription and data analysis, (5) coding and categorization, (6) phenomenological reduction, (7) descriptive and theoretical write-up, (8) interpretation and synthesis, (9) construction and reconstruction, (10) verification and validity, and (11) formulating the findings. The results revealed that teachers should master and be able to practice a combination of text, co-text, and context simultaneously to improve speech performance in language teaching. A text includes verbal skills, co-text includes non-textual and paratextual skills, and context includes situational, cultural, social, ideological, and situational skills. In language teaching-learning, teachers should effectively and informatively master speech performance by using appropriate texts, co-texts, and contexts. The study of speech performance in language teaching-learning offers a valuable understanding of the complexities of effective communication in an educational environment.